Rising Israeli–Iranian tensions. Issue 3 (16th March 2018) - Unknown
Abstract : Tensions between Israel and Iran have increased since 10 February, when Israel shot down an Iranian-made drone launched from Syria and attacked military targets there, including Iranian installations. Policymakers in both Israel and the United States believe that Iran's strategy is to make Syria a platform for war against Israel, and broadly favour rolling back Iran in Syria. In this light, the prospect of a regional war looms larger.